Pemodelan Faktor – Faktor yang Mempengaruhi Kasus Pneumonia pada Balita di Provinsi Jawa Barat dengan Metode Geographically Weighted Generalized Poisson Regression - Vergilia Agam Saputri; Purhadi Purhadi (Department of Statistics ITS, 2022)
Acute infection of lung tissue that can be caused by various microorganisms, namely fungi, viruses, and bacteria is called pneumonia. Pneumonia is the leading cause of death in children worldwide. West Java is in the top three of the number of deaths due to pneumonia in children under five in Indonesia and ranks 1st in the number of pneumonia sufferers in children under five. In solving this case, it is necessary to model with spatial effects because it is necessary to pay attention to geographical conditions in West Java, namely the GWGPR method. The highest number of pneumonia cases, as many as 10818 cases, was in Cirebon Regency while the lowest number of cases was in Banjar City as many as 573 cases. The best modeling results from the minimum AICc criteria of 483.98 are using the GWGPR method with exposure that forms two groups of districts/cities based on variables that have a significant effect on cases of pneumonia in children under five in all districts/cities, namely the percentage of vitamin A administration and the percentage of clean-living behavior and healthy.